Sedimentology of the Katberg sandstone in the Eastern Cape Province - Stavrakis, Nicholas (Rhodes University, Faculty of Science, Department of Geology, 1979)
The Katberg Sandstone is an arenaceous formation occuring stratigraphically three querters of the way up in the Beaufort Group in the south-eastern part of the main Karoo basin. A sedimentological study was carried out on the Katberg Sandstone and adjacent formations, in a 2 000 kmÂ² area south of Queenstown. Stratigraphic sections were measured and lithofacies based on the style of Miall (1977) were established for the Katberg Sandstone, Balfour and Burgersdorp Formations. Stratigraphic relationships show that the Burgersdorp Formation in the study area, is the lateral (distal) equivalent of the Katberg Sandstone. The changeover from sandstone to predominantly shale lithology occurs roughly east-west between Cathcart and Whittlesea. Stream hydraulic theory is discussed and the sedimentary structures of the various lithofacies are explained in terms of this theory. An analysis was done of thirty-four palaeochannels, and their various ancient flow characteristics were derived via multiple regression equations and a FORTRAN computer program. A statistical analysis of bedform structures, showed that flat-bedding of the upper flow regime is the dominant sedimentary structure of the Katberg Sandstone. Trough cross-bedding originating in aqueous dunes and planar cross-bedding of transverse bars, are fairly well represented while ripples are virtually absent. The opposite applies to the Balfour Formation where lower flow regime structures, viz., ripple cross-lamination and trough cross-bedding predominate. There is an even spread of (upper) flat-bedding, trough cross-bedding and ripple cross-lamination in the Burgersdorp Formation. Detailed measurement of typical short sequences from sections of the three formations, and transition matrix analyses, showed the facies assemblages to be of three stream types: (i) Katberg type: similar to Platte type of Miall (1977). Sediments were deposited by swiftly flowing, low sinuosity, braided, ephemeral streams with a predominantly sand bedload. Each flow started with preconsolidated silt and mud (flakes), and movement of exogenetic pebble lags. Channel avulsion and deposition of mud drapes in higher topographic levels of the stream were common phenomena. (ii) Balfour type: characterised by lateral accretion point bar type sequences of high sinuosity streams, and vertical accretion floodplain deposits. Lower flow regime dune and ripple bedform structures overlying (upper) flat-beds indicate a loss of stream power with channel migration. (iii) Burgersdorp type: similar to Katberg type for sandstone units, also crevasse-splays onto thick subaerially exposed floodplain aggradation reddish shales. Conventional microscopy and SEM studies showed tremendous diagenetic effects mostly in the form of secondary quartz growth in the sandstones of the three formations. Electron microprobe analyses were done on titanomagnetite grains from heavy mineral layers of the Katberg Sandstone, so that thermometric predictions could be made on provenance rocks. Palaeocurrents of the Katberg Sandstone are mostly Rank 4 and 5 types (Miall, 1974), i.e., they were generated within bars with not much change in stream orientation. Burgersdorp and Balfour formation palaeocurrents are Rank 1 - 3 types. In the case of the former this is owing to directional changes in channels as a result of frequent crevasse-splays, and in the case of the latter owing to differences in orientation between entire tracts of highly sinuous palaeostreams. Palaeocurrent directions in the Katberg Sandstone indicate a southeasterly provenance which accords with the findings of other Beaufort Group workers. Bed relief index calculations (Smith, 1970), made on Katberg rocks, considered together with the abundance of planar cross-bedding (of transverse bars) and apparent absence of longitudinal bars, testify to the deposition of the Katberg Sandstone in the distal parts of the braided stream environment. The Beaufort sediments of the study area have the sedimentological characteristics of a molasse sequence, but a different implied tectonogenesis. During Balfour sedimentation the equilibrium base was being raised very slowly at the source and complete fluvial sequences were deposited under a humid temperate climate, on a slowly subsiding plain. During Katberg/Burgersdorp times, source area tectonism was pronounced but interrupted and incomplete sequences were deposited under an arid climate. Provenance rocks for the formations studied included biotite mesoperthitic granite, granulite, charnockite, granite porphyry, granophyre, metaquartzite, greenschist and possibly diorite, epidosit e and alkaline volcanic rocks.,KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Sedimentology -- South Africa -- Eastern Cape; Geology, Stratigraphic -- South Africa -- Eastern Cape